Femoroacetabular impingement surgery allows 74% of athletes to return to the same competitive level of sports participation but their level of performance remains unreported: a systematic review with meta-analysis. Issue 15 (26th March 2018) - Reiman, Michael P; Peters, Scott; Sylvain, Jonathan; Hagymasi, Seth; Mather, Richard C; Goode, Adam P
Abstract : Background: Femoroacetabular impingement (FAI) syndrome is one source of hip pain that can limit sport participation among athletes. Objective: To summarise the return to sport (RTS) rate for athletes after surgery for FAI syndrome. Methods: A computer-assisted search of MEDLINE, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and EMBASE databases was performed using keywords related to RTS and RTS at preinjury level (RTSPRE ) of competition for FAI syndrome. The risk of bias in the included studies was assessed using the Methodological Index for Non-Randomized Studies scale. Results: 35 studies (1634 athletes/1828 hips) qualified for analysis. Based on evidence of limited to moderate strength (level 3b to 4 studies), athletes return to sport at preinjury level post surgery for FAI syndrome at a rate of only 74% (67%–81%). Only 37% of studies reported RTSPRE . The mean time from surgery to RTS was 7.0±2.6 months. The mean follow-up postsurgery was 28.1±15.5 months. Professional athletes returned to sport (p=0.0002) (although not the preinjury sport level; p=0.63) at a higher rate than collegiate athletes. Only 14% of studies reported on athletic presurgery and postsurgery athletic performance, which means it is impossible to comment on whether athletes return to their previous level of performance or not. No studies reported on the specific criteria used to permit players to return to sport. 20% of studies reported on career longevity, 51% reported surgical complications and 77% reported on surgical failures. Conclusion: There was limited to moderate evidence that one in four athletes did not return to their previous level of sport participation after surgery for FAI syndrome. Only 37% of the included studies clearly distinguished RTS from RTSPRE . Poor outcome reporting on athletic performance postsurgery makes it difficult to determine to what level of performance these athletes actually perform. Thus, if a player asks a surgeon 'Will I get back to my previous level of performance?' there are presently little to no published data from which to base an answer. PROSPERO registration number: CRD42017072762.